2011
DOI: 10.3109/01443615.2011.568644
|View full text |Cite
|
Sign up to set email alerts
|

Preoperative vaginal preparation with povidone-iodine on post-caesarean infectious morbidity

Abstract: The commonest complication associated with caesarean section is infection. The aim of this study is to investigate the effect of vaginal preparation with povidone-iodine on post-caesarean infection. In this clinical trial, 568 patients were selected for two groups: a treatment group and a control group, each with 284 patients. A vaginal scrub was performed before the routine abdominal scrub, with two 4 × 4 cm sponge sticks saturated with povidone-iodine solution, rotated in the vagina for about 30 s. In the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2013
2013
2020
2020

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(19 citation statements)
references
References 12 publications
0
18
0
Order By: Relevance
“…All trials compared preoperative vaginal washing with povidone-iodine solution with no vaginal washing in six trials and one trial with preoperative vaginal washing with saline solution. [7,16] Such studies findings revealed that the incidence of post-caesarean endometritis significantly decreased in those subjects who scrubbed with both abdominal and vaginal with povidoneiodine, compared with those who received a standard abdominal scrub alone. Consistent with this finding a randomized controlled trial in USA on 160 parturient women with cesarean section were randomized to vaginal washing with either Povidone-Iodine (n = 80) or saline (n = 80).…”
Section: Discussionmentioning
confidence: 79%
See 1 more Smart Citation
“…All trials compared preoperative vaginal washing with povidone-iodine solution with no vaginal washing in six trials and one trial with preoperative vaginal washing with saline solution. [7,16] Such studies findings revealed that the incidence of post-caesarean endometritis significantly decreased in those subjects who scrubbed with both abdominal and vaginal with povidoneiodine, compared with those who received a standard abdominal scrub alone. Consistent with this finding a randomized controlled trial in USA on 160 parturient women with cesarean section were randomized to vaginal washing with either Povidone-Iodine (n = 80) or saline (n = 80).…”
Section: Discussionmentioning
confidence: 79%
“…[6] The most common maternal morbidity arising from CS is infection. [7] In fact, cesarean delivery is the most significant risk factor for postpartum infection. [8] Postpartum infection has been shown to be eight-folds higher after surgical delivery than after normal delivery.…”
Section: Introductionmentioning
confidence: 99%
“…Intravaginal povidone‐iodine has already been used as a preoperative antiseptic to reduce postsurgery endometritis after caesarean sections (Asghania et al . ) and histerectomy (Sowapat et al . ) and as a treatment of bacterial vaginosis.…”
Section: Resultsmentioning
confidence: 99%
“…In conclusion, our results showed that povidone-iodine had the widest antichlamydial therapeutic index and could maintain an antichlamydial effect when used intravaginally. Intravaginal povidone-iodine has already been used as a preoperative antiseptic to reduce postsurgery endometritis after caesarean sections (Asghania et al 2011) and histerectomy (Sowapat et al 2006) and as a treatment of bacterial vaginosis. Povidone-iodine also can be attractive in bacterial vaginosis treatment because it has no significant antimicrobial activity against lactobacilli (Sakakura et al 1993;Wewalka et al 2002).…”
Section: Chlamycount Immunofluorescent Measurement Of the Impact Of Amentioning
confidence: 99%
“…She also had vaginal cleaning before the Caesarean section as well as insertion of a urinary catheter. It has been shown that preoperative vaginal preparation with povidone-iodine decrease the risk of developing endometritis but has no effect on wound infection rate [4]. Post-operative uterine wall dehiscence is reported to be around 0.6%.…”
Section: Discussionmentioning
confidence: 99%